THE STANDARD C.P.A. EXAMINATION. - Zebley, John H. (The Accounting Review, 1941)
Abstract Forty-four states in the U.S. and territories and the District of Columbia have adopted as their written examination for candidates for the certified public accountant certificate the standard examination prepared by the American Institute of Accountants. The committee on enrollment and disbarment of the Treasury Department has recently adopted the Institute's problems in accounting theory and practice as a part of its examinations for candidates for a treasury card who are not members of the Bar nor certified public accountants. The responsibility for producing the standard examination rests with the Institute's board of examiners. The Institute's board believes that the certified public accountant certificate should signify that its holder is qualified to practise public accounting and has passed an examination that tests his practical ability as well as his theoretical knowledge. Members of a number of state boards have suggested that the standard of knowledge and ability properly expected of a candidate for the certified public accountant certificate should be that of a senior staff accountant, and the standard examination is intended to require ability of about that level.